FAKTOR EKSTERNAL DAN INTERNAL YANG MEMPENGARUHI MOTIVASI BERPRESTASI PEGAWAI PADA DINAS BINA MARGA DAN PENGAIRAN KABUPATEN ROKAN HULU - -, HENDRA (Jurnal Mahasiswa Prodi SI Manajemen, 2013)
This research entitle “ Influence of Factor of Eksternal and Internal to motivation have officer achievement [to] [at] On duty Construct Clan and Irrigating Of Sub-Province of Rokan Pate;Upstream”. This Research aim to to know motivation have officer achievement [to] [at] On duty Construct Clan and Irrigating Of Sub-Province of Rokan Pate;Upstream as well as to know Influence of Factor of Eksternal and Internal to motivation have officer achievement [to] [at] On duty Construct Clan and Irrigating Of Sub-Province of Rokan Pate;Upstream. Population in this research is entire/all officer [at] On duty Construct Clan and Irrigating Of Sub-Province of Rokan Pate;Upstream amounting to 82 people, taken Sampel counted 82 people by using research kusioner with scale of likert data and analysed with technique analyse doubled linear regresi.Pursuant to research result, obtained that factor influencing motivation have officer achievement [to] [at] On duty Construct Clan and Irrigating Of Sub-Province of Rokan Pate;Upstream is both factor that is factor of Eksternal and Internal which have an effect on positive to officer performance. With the model variant analysis have the character of enough isn´t it with determinasi koefisient equal to 0,124 meaning that 12,4% variation [of] [at] Y can be explained with model, while the rest 87,6% [do] not earn to be explained with model. This research still limited to focussed [at] influence of factor of eksternal and internal to motivation have officer achievement [to], expected for research to come can be [done/conducted] [by] repair and suggested to add other independent variable.